Isostatically disturbed terrain of northwestern andes mountains from spectrally correlated free-air and gravity terrain data (2006)
Recently revised models on global tectonics describe the convergence of the North Andes, Nazca, Caribbean and South American Plates and their seismicity, volcanism, active faulting and extremetopography. The current plate boundaries of the area are mainly interpreted from volcanic and seismic datasets with variable confidence levels. New insights on the isostatic state and plate boundaries ofthe northwestern Andes Mountains can be obtained from the spectral analysis of recently available gravity and topography data. Isostatically disturbed terrain produces free-air anomalies that are highly correlated with the gravity effects of the terrain. The terrain gravity effects (TGE) and free air gravity anomalies (FAGA) of theAndes mountains spectral correlation data confirms that these mountains are isostatically disturbed. Strong negative terrain-correlated FAGA along western South America and the Greater and Lesser Antilles are consistent with anomalously deepened mantle displaced by subducting oceanic plates. Inversion of the compensated terrain gravity effects (CTGE) reveals plate subduction systems with alternating shallower and steeper subduction angles. The gravity modeling highlights crustaldeformation from plate collision and subduction and other constraints on the tectonism of the plate boundary zones for the region.